DINAMIKA PEMBENTUKAN UNDANG-UNDANG PERKAWINAN YORDANIA: Integrasi Nilai Syari’ah dan Standar Hak Asasi Manusia - Dliya'uddin Achmad; Umul Baroroh; Agus Nurhadi; Achmad Tubagus Surur (PT Taskuliah Edukasi Indonesia, 2025)
This study analyzes the dynamics of the formation of Jordan's Marriage Law in the context of tensions between Sharia values and human rights standards. The complex political negotiations in the process of forming Jordan's marriage law between reformist groups promoting gender equality in accordance with CEDAW, and religious authorities and conservative groups adhering to classical fiqh interpretations, make Jordan a crucial case study for understanding the dialectic of law in the modern Muslim world. Using a socio-historical approach and descriptive qualitative methods, this literature study examines the legislative process of Law No. 36/2010. The results show that the harmonization achieved is partial and represents a political compromise rather than a complete philosophical integration. Reforms such as the standardization of the age of marriage accompanied by a dispensation clause reflect the state's negotiation between the demands of human rights activists and conservative religious resistance. The study concludes that this law represents an evolutionary modern ijtihad, in which normative reconciliation is more of a negotiation of interests, so that the future of Jordanian family law is expected to continue to follow a pattern of gradual and compromising reform. [Penelitian ini menganalisis dinamika pembentukan Undang-Undang Perkawinan Yordania dalam konteks ketegangan antara nilai syariah dan standar Hak Asasi Manusia (HAM). Negosiasi politik yang kompleks dalam proses pembentukan undang-undang perkawinan Yordania antara kelompok reformis yang mendorong kesetaraan gender sesuai CEDAW, dengan otoritas keagamaan dan kelompok konservatif yang berpegang pada interpretasi fiqh klasik, membuat Yordania menjadi studi kasus yang krusial untuk memahami dialektika hukum di dunia Muslim modern. Pendekatan sosio-historis dan metode dualitatif deskriptif, studi kepustakaan ini mengkaji proses legislasi UU No. 36/2010 digunakan dalam penelitian ini. Hasil penelitian menunjukkan bahwa harmonisasi yang dicapai bersifat parsial dan merupakan kompromi politik, bukan integrasi filosofis yang utuh. Reformasi seperti penyeragaman usia nikah diiringi klausul dispensasi, mencerminkan negosiasi negara antara desakan aktivis HAM dan resistensi konservatif agama. Simpulan penelitian menyatakan bahwa UU ini merepresentasikan ijtihad modern yang evolutif, di mana rekonsiliasi normatif lebih merupakan negosiasi kepentingan, sehingga masa depan hukum keluarga Yordania diperkirakan akan tetap mengikuti pola reformasi bertahap dan kompromistis].